2003
DOI: 10.1210/jc.2002-021561
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Serum Paraoxonase 1 Activities and Increased Oxidized Low-Density Lipoprotein Levels in Impaired Glucose Tolerance and Newly Diagnosed Diabetes Mellitus

Abstract: Several in vitro investigations showed that serum paraoxonase 1 (PON1) that is located on high-density lipoprotein reduces or prevents low-density lipoprotein (LDL) oxidation and therefore retards atherosclerosis. Accordingly, the well documented loss of PON1 activity in patients with overt diabetes mellitus was causally related to the development of micro- and macroangiopathy in the disease course. Because vascular complications start already in prediabetic states, e.g. impaired glucose tolerance (IGT), we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 33 publications
5
28
2
2
Order By: Relevance
“…PON and PAF-AH activities have inconstantly been found to be decreased and related to HDL antioxidant capacity in type 2 diabetic patients [11,[27][28][29]. Interestingly, in type 2 diabetic patients, the antioxidant capacity of HDL can be decreased, whereas PON and PAF-AH activities are similar to those measured in controls [11], indicating that in type 2 diabetes mellitus other factors than the decrease of PON and PAF-AH activities are likely to impair HDL antioxidant activity.…”
Section: Discussionmentioning
confidence: 90%
“…PON and PAF-AH activities have inconstantly been found to be decreased and related to HDL antioxidant capacity in type 2 diabetic patients [11,[27][28][29]. Interestingly, in type 2 diabetic patients, the antioxidant capacity of HDL can be decreased, whereas PON and PAF-AH activities are similar to those measured in controls [11], indicating that in type 2 diabetes mellitus other factors than the decrease of PON and PAF-AH activities are likely to impair HDL antioxidant activity.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, PON1 activity was also reported to be similar in diabetic patients, in subjects with impaired fasting glucose, and in normoglycemic controls [28,29], which suggested the loss of PON1 activity to occur later in the course of DM and hyperglycemia rather than in the stage of insulin resistance [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Oxidation of HDL in diabetic pa tients causes a change in the PON1 protein and an ensuing drop in PON1 activity (79). PON1 activity was shown to decrease in type 1 and type 2 diabetes patients in several studies, while some other studies reported that PON1 activity was not related to type 1 and type 2 diabetes (82)(83). Apart from that, it was noted in some studies that diabetes was correlated with PON1 polymorphism, although other studies failed to confirm this correlation (84-86).…”
Section: Clinical Significancementioning
confidence: 99%